Audição periférica e central de frentistas - Quevedo, Lenita da Silva (2011)
This work had as aim the evaluation of the central and peripheral hearing system of the subjects exposed to fuels. It was a prospective study, where attendants of three gas stations from Santa Maria were evaluated. After the adaptation to the inclusion criteria, the sample was composed of 24 subjects. A control group, of 24 was used in order to compare the results. The applied examinations were: Pure Tone Audiometry (PTA), Impedance Audiometry, research on acoustic reflexes, audiometry of high frequencies and the Auditory Brain Response (ABR). The average threshold of the study group was superior to the control group. The same occurred to the average thershold of the audiometry of high frequencies, in the range 9 to 14 kHz. In the frequencies from 16 to 20 kHz, the occurence of absent responses was higher in the study group in both ears. When compare in relation to the time of exposition, the average thresholds in high frequencies (9-14kHz) had significant statistical difference (p <0.05) in all the frequencies (9-14 kHz), when compared the control group to the study group. It was observed a greater absence of ipsilateral and contralateral acoustic reflexes in the right ear. In the left ear, there was no difference between the groups, concerning the occurrence of the ipsilateral reflex. The absence of contralateral reflex was bigger in the study group in all the teste frequencies. In the ABR, there was a change in the absolute latencies of Waves I and III and in all the interpeak latencies, in the right ear. In the left ear there was a change in the absolute latency of all the waves, and in all the interpeaks. The absolute latency of Wave III had greater occurrence of change, in both ears. The interaural difference of Wave V had a change in 19% of the subjects. The group exposed to fuels for at least three years demonstrated a change in the III-V interpeak of the right ear and in the absolute latency of Wave V in the left ear. In the group exposed for more than five years, the number of subjects with a change was statistical significant in: I-V interpeak of the right ear; absolute latency of Wave I and interpeak III-V of the left ear. It was verified that the subjects exposed to fuels had a statistically significant change in the average hearing thresholds in the frequencies 0.5 kHz (p=0.004), 2 kHz (p=0.001), 3 kHz (p=0.025), 9 kHz (p=0.007) and 10 kHz (p=0.026). In the ABR, it was observed a significant statistical difference in the interpeak III-V of the right ear (p=0.027) and the absolute latency of Wave V in the left ear (p=0.0257), in the group exposed for at least three years. In the group exposed for more than five years it was statistically significant the number of subjects with change in the I-V interpeak of the right ear (p=0.0173), in the absolute latency of Wave I and in the III-V interpeak of the left ear ( p=0.0173).